Before There Were Kings: A Literary Analysis of the Book of Judges - Assis, Elie (Bulletin for Biblical Research Supplement, 2023)
Following the great periods of national leadership by Moses and Joshua, the book of Judges depicts the stewardship of various judges that rose to power to solve local religious and military challenges in the premonarchic period. This volume provides a close reading of the entire book of Judges, taking seriously the distinct elements of the book and how they are interconnected. Elie Assis explores the ways in which the ideology and theology of Judges unfold through a careful literary analysis. Moving beyond the cycle of sin, punishment, and salvation, Assis demonstrates how differences in the descriptive language applied to each judge, as well as the evaluations in the opening and concluding chapters, provide clues as to the organization and message of the text. Most works on Judges focus on the historical background of the period or the historical process of the book's composition and seek to dissolve its stories into component parts. In contrast, Before There Were Kings points to the deep underlying unity of Judges and the function of the individual stories within the whole. New and carefully drawn insights related to the purpose of each section and the themes that shape the book as a whole make this a groundbreaking, programmatic contribution to research on the book of Judges. It will be of particular interest to students and scholars of the Old Testament and the Hebrew Bible.